'Stars' and places: exploring the spatial organization of media and entertainment industries in China. Issue 5 (2nd September 2020) - Zhang, Xu; Kloosterman, Robert C.; Li, Yajuan
ABSTRACT: Drawing on an innovative 'big data' method, this paper presents a comprehensive analysis of the geography of media and entertainment industries (MEIs) in China, by examining the specific activities that are performed by celebrities, the key actors in these industries. Compared to previous research on cultural and creative industries, which primarily rely on more traditional statistical data, our study demonstrates a new approach to systemically investigate the spatial organization of the dynamic production process in MEIs. The outcomes reveal that activities focusing on the different value segments of MEIs display rather diverse geographical patterns. Depending on the availability and combination of specific local assets, different locations perform varying functions in the production networks of MEIs. Therefore, the agglomeration of MEIs only partially overlaps with the existing urban hierarchy. In addition, celebrities catering to different media and entertainment markets also exhibit distinct activity patterns, indicating a close and reciprocal relationship between the popularity of celebrities, the activities they perform, the platforms that are chosen, and the commercial value that can be generated as a result. This study contributes to our understanding of the complex development patterns and consequences of MEIs in emerging economies.